Granzyme B Functionalized Nanoparticles Targeting Membrane Hsp70‐Positive Tumors for Multimodal Cancer Theranostics. Issue 13 (4th March 2019) - Shevtsov, Maxim; Stangl, Stefan; Nikolaev, Boris; Yakovleva, Ludmila; Marchenko, Yaroslav; Tagaeva, Ruslana; Sievert, Wolfgang; Pitkin, Emil; Mazur, Anton; Tolstoy, Peter; Galibin, Oleg; Ryzhov, Vyacheslav; et al.
Abstract: Functionalized superparamagnetic iron oxide nanoparticles (SPIONs) have emerged as potential clinical tools for cancer theranostics. Membrane‐bound 70 kDa heat shock protein (mHsp70) is ubiquitously expressed on the cell membrane of various tumor types but not normal cells and therefore provides a tumor‐specific target. The serine protease granzyme B (GrB) that is produced as an effector molecule by activated T and NK cells has been shown to specifically target mHsp70 on tumor cells. Following binding to Hsp70, GrB is rapidly internalized into tumor cells. Herein, it is demonstrated that GrB functionalized SPIONs act as a contrast enhancement agent for magnetic resonance imaging and induce specific tumor cell apoptosis. Combinatorial regimens employing stereotactic radiotherapy and/or magnetic targeting are found to further enhance the therapeutic efficacy of GrB‐SPIONs in different tumor mouse models. Abstract : 70 kDa heat shock protein is expressed on tumour cell membranes, but not on corresponding normal cells, and thus could be exploited for development of theranostic agents. Serine protease granzyme B conjugated with superparamagnetic iron oxide nanoparticles is shown to specifically target tumors. A combination of nanoparticles with radiotherapy and/or magnetic targeting significantly enhances the therapeutic potential of the nanocarriers.